2018
DOI: 10.1101/274266
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spinocerebellar ataxia type 11-associated alleles of Ttbk2 dominantly interfere with ciliogenesis and cilium stability

Abstract: Spinocerebellar ataxia type 11 (SCA11) is a rare, dominantly inherited human ataxia characterized by atrophy of Purkinje neurons in the cerebellum. SCA11 is caused by mutations in the gene encoding the Serine/Threonine kinase Tau tubulin kinase 2 (TTBK2) that result in premature truncations of the protein. We previously showed that TTBK2 is a key regulator of the assembly of primary cilia in vivo. However, the mechanisms by which the SCA11-associated mutations disrupt TTBK2 function, and whether they interfere… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 38 publications
3
29
0
Order By: Relevance
“…Ttbk2 is essential both for the initiation of cilium assembly as well as for the structure and stability of cilia (Bowie et al, 2018;Goetz et al, 2012). Consistent with this, we have found that primary cilia are lost from cells within the cerebellum of Ttbk2 cmut mice ( Figure 5) prior to the onset of the phenotypes we observe in neuronal connectivity and survival.…”
Section: Loss Of Ift88 Recapitulates Ttbk2 Cmut Phenotypessupporting
confidence: 84%
See 4 more Smart Citations
“…Ttbk2 is essential both for the initiation of cilium assembly as well as for the structure and stability of cilia (Bowie et al, 2018;Goetz et al, 2012). Consistent with this, we have found that primary cilia are lost from cells within the cerebellum of Ttbk2 cmut mice ( Figure 5) prior to the onset of the phenotypes we observe in neuronal connectivity and survival.…”
Section: Loss Of Ift88 Recapitulates Ttbk2 Cmut Phenotypessupporting
confidence: 84%
“…In this work, we present evidence that loss or impaired function of TTBK2 within the brain results in degeneration of PCs due largely to the requirement for TTBK2 in mediating the assembly and stability of primary cilia. This points to ciliary dysfunction as being a major mechanism underlying the pathology of SCA11, which is caused by truncating mutations to TTBK2 (Houlden et al, 2007) that act as dominant negatives (Bowie et al, 2018). In addition, our work raises the possibility that cilia play an important, largely unappreciated role in maintaining neuronal connectivity within the brain, and may also be required for the viability of some types of neurons.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations